Pengaruh Kebisingan terhadap Stres Kerja Guru di Sekolah X Kabupaten Serdang Bedagai - Ad’dhan Dhita; Tri Niswati Utami (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2026)
This study was conducted to analyze the effect of noise on the level of work stress of teachers at School X, Serdang Bedagai Regency. The method used was a quantitative approach with a cross-sectional research design, involving 50 teachers as respondents selected through a total sampling technique. Data were collected through noise measurements using a Sound Level Meter and the distribution of work stress questionnaires referring to the Minister of Manpower Regulation Number 5 of 2018. The measurement results showed that the noise intensity at several points exceeded the safe threshold, which was 55 dBA. However, the results of a simple linear regression analysis showed that noise did not have a significant effect on teacher work stress, with a significance value (p) of 0.481 (p > 0.05) and a coefficient of determination (R²) of 0.010. These findings indicate that other factors outside of noise are more dominant in influencing teacher work stress levels. Therefore, it is recommended that efforts to manage teacher stress be focused on non-physical factors, such as workload management, organizational support, and developing teacher mental well-being, in addition to maintaining the quality of the school environment to be more conducive.